Soil-water retention curve and beginning of monitoring in Tierra Blanca Joven (TBJ) - Chávez, José A. (2011)
In El Salvador during the rainy season or when major earthquakes occur, the areas covered by the volcanic tephras Tierra Blanca Joven (TBJ) suffer mass movements, liquefaction and erosion; causing important en- vironmental, social and economic losses. To start the characterization of these unsaturated soils, suction values of a fall unit of TBJ were obtained using pressure plate, centrifuge and filter paper to build a Soil-Water Retention Curve. The use of this curve into finite elements software can help to acquire shear strength and permeability properties. The filter paper showed to be a practical method but close to saturation the pressure plate is needed. With the centrifuge, scatter results were observed. Also field test using Quickdraw tensiometer (suction) and TMS3 (soil moisture content) are being conducted to propose a field methodology for an early warning system for the slopes, that could help in urban planning and risk assessment.